Menakar Makna Adil Dalam Keluaga Berpoligini: Perbandingan Pandangan Antara Prof. Dr, Tm. Hasbi Ash-Shiddiqy Dan Prof. Dr. Hamka - Samheri, Samheri; Mawaddah, Mawaddah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
In Islamic shari'ah there are two forms of marriage, namely polygamy and monogamy, of which polygamy is the marriage of a man to several women, commonly called